Sosialitas dalam Perspektif Filsafat Sosial - Siswanto, Dwi (Jurnal Filsafat "WISDOM", 2004)
The human sociality is one element that makes man different with other creature; so that the sociality is the man nature.The human sociality process a great dimension. Man was called human being as far as build a relation with other. Man is impossible to live alone. Proverb said' "No man is an island"There are many thoughts about a human society princple like conflict, love, face to face asymmetric relation, solidarity, and subsidiary as examples.Man and his society are two reality that influenced each other. They construct a dynamic horizon in dialectics relation. Man and his society is two moment complement. Their main principle is, man not only co-existence, but also co-operative. According to the principlesÂ  of love, solidarity, and subsidiary those principle must be safeguarded and improved as an ideal basic for sociality.